Sexual Harassment of Female Employees in the Workplace: Imperative For Stringent Legal And Policy - Enobong Mbang Akpambang (Pancasila and Law Review)
This article presents the challenges associated with work-related sexual harassment of female employees and assess whether binding legislative and policy frameworks exist to address the issue in Nigeria. To achieve this objective, the research employs both doctrinal and comparative approaches, reviewing relevant literature and comparing Nigeria’s legal position with that of selected foreign jurisdictions with established anti-harassment legislation. Additionally, theoretical models are utilized to explain potential causes of sexual harassment. The findings indicate that sexual harassment in the workplace has been extensively studied both domestically and internationally, with data revealing its prevalence in both public and private sectors and its significant negative impact on employers as well as the health and psychological well-being of employees. The research highlights that, unlike other countries, Nigeria lacks specific anti-sexual harassment legislation, and existing national legal frameworks addressing sexual offenses are insufficient to effectively combat the problem. Consequently, the article recommends the implementation of stringent legal and policy measures in Nigeria to address the multifaceted issue of workplace sexual harassment, drawing on practices observed in the three foreign jurisdictions examined.